Football as social sport culture phenomenon - Nazarenko, L. D.; Kolesnik, I. S. (Theory and Practice of Physical Culture, 2018)
It was for the first time in 2018 that Russia hosted a FIFA World Cup, and every football fan in the nation hoped the national team would be able to make it at least to the top 8. It was beyond all hopes to see the national team so highly competitive, determined, confident and eager to win. Objective of the study was to explore the fast progress of the Russian national team to the world football elite. The analysis was supported by statistics of the world best teams in the FIFA World Cup; comparative analysis of the Russian team competitive performance versus the other national teams; and a progress analysis of the Russian team ascendance in the 2018 FIFA World Cup. We believe that it was the national team success in the match with Spain that demonstrated fast progress made by the Russian football to win a place in the global elite. The success was once again proved in the highly competitive match with Croatia that demonstrated that the enthusiastic crowd support and determination of every player may secure success in a top-ranking global event.